KAJIAN SIFAT FISIKOKIMIA DAN ORGANOLEPTIK ES KRIM PISANG TONGKA LANGIT - Helen C D Tuhumury; Sandriana J Nendissa; Mardila Rumra (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
This research was aimed to determine the accurate ratio of concentration of tongka langit banana puree and water that would result in ice cream having good quality and would be preferred by consumers. A Completely Randomized experimental design having four levels of concentration ratio of tongka langit banana: water, i.e. 3%:52%, 5%:50%, 7%:48%, and 10%:45% was applied. Respective variables observed were chemical properties (protein, fat, vitamin C, and total solids contents), sensory properties (color, taste, texture, and overall acceptance), as well as physical properties (resistance / rate of melting). Results showed that the ratio of 7% : 48% was determined as the best ratio to produce ice cream with the best physicochemical and sensory properties.